MiR-155 Regulates PAD4-Dependent Formation of Neutrophil Extracellular Traps - Hawez, Avin; Al-Haidari, Amr; Madhi, Raed; Rahman, Milladur; Thorlacius, Henrik (Frontiers in Immunology, 2019)
Accumulating data suggest that neutrophil extracellular traps (NETs) play a key role in several diseases. Peptidylarginine deiminase 4 (PAD4) regulates NET formation via citrullination of histones. The aim of this study was to examine the role of miR-155 in controlling PAD4-dependent generation of NETs. Bone marrow neutrophils were stimulated with PMA and MIP-2. Pre-incubation of neutrophils with translational inhibitors (cycloheximide or puromycin) markedly decreased NET formation induced by PMA or MIP-2. Neutrophil transfection with a mimic miR-155 increased PMA-induced PAD4 mRNA expression and NET formation. In contrast, transfection with an antagomiR-155 decreased induction of PAD4 mRNA and NETs in response to PMA challenge. Bioinformatics analysis predicted a putative binding site in AU-rich elements at the 3´-UTR of PAD4. MiR-155 binding to PAD4 was verified using target site blockers and functionally validated using RNA immunoprecipitation assays, showing that miR-155-dependent regulation of PAD4 mRNA is mediated by AU-rich elements present in the 3´-UTR region. In conclusion, our results demonstrate that miR-155 positively regulates neutrophil expression of PAD4 and expulsion of extracellular traps. Thus, our novel findings suggest that miR-155 could be used to inhibit exaggerated NET generation in inflammatory diseases.